2022
DOI: 10.1038/s41598-022-15122-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body position on the redistribution of regional lung aeration during invasive and non-invasive ventilation of COVID-19 patients

Abstract: Severe COVID-19-related acute respiratory distress syndrome (C-ARDS) requires mechanical ventilation. While this intervention is often performed in the prone position to improve oxygenation, the underlying mechanisms responsible for the improvement in respiratory function during invasive ventilation and awake prone positioning in C-ARDS have not yet been elucidated. In this prospective observational trial, we evaluated the respiratory function of C-ARDS patients while in the supine and prone positions during i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…These results are consistent with the recent study from Dos Santos Rocha et al, who found no differences in regional distribution of aeration after awake pronation, while observed signi cantly increase in dorsal fraction of ventilation in mechanically ventilated patients [29], as we measured in our previous study [5]. A possible explanation could be attributable to the different stages of the disease: in ventilated patients the bene cial effects of pronation are consistent with recruitment of atelectatic alveoli; in mild to moderate ARDS, prone position may help to divert blood ow towards less damaged zones [30].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the recent study from Dos Santos Rocha et al, who found no differences in regional distribution of aeration after awake pronation, while observed signi cantly increase in dorsal fraction of ventilation in mechanically ventilated patients [29], as we measured in our previous study [5]. A possible explanation could be attributable to the different stages of the disease: in ventilated patients the bene cial effects of pronation are consistent with recruitment of atelectatic alveoli; in mild to moderate ARDS, prone position may help to divert blood ow towards less damaged zones [30].…”
Section: Discussionsupporting
confidence: 93%
“…EIT has been investigated in ventilated patients with COVID-19 [ 13 ], but investigations on non-intubated and spontaneously breathing patients are scarce [ 14 , 15 ]. Therefore, the main objective of the study was to evaluate lung inhomogeneity assessed by EIT in COVID-19 patients with ARF in a supine position (SP) and PP.…”
Section: Introductionmentioning
confidence: 99%
“…Combining a CT scan and EIT, Fossali et al showed that PP effects on COVID-19 patients are mainly driven by improved ventilation:perfusion matching [ 31 ]. Finally, using EIT and an intrapulmonary shunt calculation (based on a modified Berggren equation), a recent study confirmed that PP is associated with a reduction in an intrapulmonary shunt [ 32 ]. Thus, the pulmonary blood flow could be diverted away from the reaerated lung regions in PP, resulting in ventilation:perfusion matching alteration [ 33 ].…”
Section: Discussionmentioning
confidence: 97%